Pengaruh Gaya Kepemimpinan, Kompensasi, dan Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Motivasi Kerja Sebagai Variabel Intervening di Koperasi Jasa Tri Capital Investama - Dewi Purnamasari; Hwihanus (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
The purpose of this study is to describe the Tri Capital Investama Services Cooperative's leadership style, compensation, work environment, employee performance, and work motivation. It also seeks to evaluate and assess the impact of these factors on the motivated employees' performance. serve as a variable in between. Using census methodology, the study's sample consisted of 60 workers of Tri Capital Investama Services Cooperative, while the study's population comprised all 60 employees. Then, partial least squares – structural equation model (PLS-SEM) is used to evaluate the acquired data. The study's findings indicate that Tri Capital Investama Services Cooperative employees have high levels of work motivation, compensation, work environment, and leadership style. However, work motivation at the cooperative does not significantly impact employee performance due to leadership style. In the Tri Capital Investama service cooperative, pay has a big impact on workers' incentive to perform well at work. At the Tri Capital Investama service cooperative, the workplace has a big impact on workers' productivity through work motivation.